2019
DOI: 10.1177/0190272519868988
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the Black Box: Capturing the Role of Expectation States in Status Processes

Abstract: A fundamental task for sociology is to uncover the mechanisms that produce and reproduce social inequalities. While status characteristics theory is the favored account of how social status contributes independently to the maintenance of inequality, it hinges on an unobserved construct, expectation states, in the middle of the causal chain between status and behavior. Efforts to test the mediation mechanism have been complicated by the implicit, often unconscious, nature of status expectations. To solve this “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…This may be ephemeral or, more interestingly, a system may come to saturate the construction and maintenance of an autobiography or collective biography, and it may have consequences for how we project self, attune with others, and consciously or unconsciously do bodily language. In turning to embodiment, however, we were also able to consider some aspects of cognitive neuroscience that could contribute to ongoing work in neurosociology building on symbolic interactionism (Neimeyer, 2013;Kalkhoff et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be ephemeral or, more interestingly, a system may come to saturate the construction and maintenance of an autobiography or collective biography, and it may have consequences for how we project self, attune with others, and consciously or unconsciously do bodily language. In turning to embodiment, however, we were also able to consider some aspects of cognitive neuroscience that could contribute to ongoing work in neurosociology building on symbolic interactionism (Neimeyer, 2013;Kalkhoff et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lents, 2016;de Waal 2019). Complementing this theoretical work, the emerging field of neurosociology has begun to specify the location and functioning of key processes and theoretical constructs in social psychological theory using neuroscientific methods (Kalkhoff et al , 2019Niemeyer 2013). These include self-verification in identity theory (Burke and Stets 2009), expectation states in status characteristics theory (Berger et al 1972), and solidarity in the affect theory of exchange (Lawler 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence links performance expectations to status, which in turn leads to social influence. Kalkhoff et al (2020) showed that self-reported expectations for partner performance were positively associated with publicly accepting the influence of a partner. Ridgeway (1982) showed that the perceived motivations of group members contribute to their relative levels of influence.…”
Section: Status and Influencementioning
confidence: 99%
“…Dozens of small group studies confirm the association between status and behavioral inequalities (Berger and Webster 2018), and the theory has been applied to explain racial and gender inequalities (e.g., Correll 2004; Lovaglia et al 1998). But measuring the culturally informed expectations placing individuals in a group’s status hierarchy poses at least three problems (Kalkhoff et al 2020). First, such expectations are not usually conscious; measuring them with a questionnaire is problematic.…”
mentioning
confidence: 99%
“…group's status hierarchy poses at least three problems (Kalkhoff et al 2020). First, such expectations are not usually conscious; measuring them with a questionnaire is problematic.…”
mentioning
confidence: 99%